Bridging the Gap: A Systematic Review on Reporting Baseline Characteristics, Process, and Outcome Parameters in Rectosigmoid Hirschsprung's Disease - Rossi, Daniel; Löf Granström, Anna; Teunissen, Nadine M.; Wijnen, René M.H.; Wester, Tomas; Sloots, Cornelius E.J. (European Journal of Pediatric Surgery, 2024)
The variation in standardized, well-defined parameters in Hirschsprung's disease (HSCR) research hinders overarching comparisons and complicates evaluations of care quality across healthcare settings. This review addresses the significant variability observed in these parameters as reported in recent publications. The goal is to compile a list of commonly described baseline characteristics, process and outcome measures, and to investigate disparities in their utilization and definitions. A systematic review of literature on the primary care process for HSCR was performed according to PRISMA guidelines. Relevant literature published between 2015 and 2021 was obtained by combining the search term “Hirschsprung's disease” with “treatment outcome,” “complications,” “mortality,” “morbidity,” and “survival” in Medline, Embase, and the Cochrane Library. We extracted study characteristics, reported process and outcome parameters, and patient and disease characteristics. We extracted 1,026 parameters from 200 publications and categorized these into patient characteristics (n = 226), treatment and care process characteristics (n = 199), and outcomes (n = 601). A total of 116 parameters were reported in more than 5% of publications. The most frequently reported characteristics were sex (88%), age at the time of surgery (66%), postoperative Hirschsprung-associated enterocolitis (64%), type of repair (57%), fecal incontinence (54%), and extent of aganglionosis (51%). This review underscores the pronounced variation in reported parameters within HSCR studies, highlighting the necessity for consistent, well-defined measures and reporting systems to foster improved data interpretability. Moreover, it advocates for the use of these findings in the development of a Core Indicator Set, complementing the recently developed Core Outcome Set. This will facilitate quality assessments across pediatric surgical centers throughout Europe.
Keywords: Hirschsprung's disease; outcome; characteristics